ANALISIS KEGIATAN HUMAS UNIVERSITAS ISLAM NEGERI SUMATERA UTARA DALAM MENINGKATKAN REPUTASI LEMBAGA - Muzhaffar, Hanif; Efendi, Erwan (UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
Reputation is a very valuable asset for all universities, with a good reputation not only increasing public trust but also attracting prospective students, cooperation partners and increasing the power of higher education at the national and international levels. In this case the role of public relations and other units in the institution becomes very important in building, maintaining and improving the reputation of a college in order to be able to compete with other universities, through public relations activities to internal audiences and external audiences external public as the target of its activities, in this study the researcher wants to examine what the strategy of public relations activities of UIN SU in building the reputation of North Sumatra State Islamic University, this research uses descriptive qualitative research type. In addition, this research uses several things to be able to obtain data, namely interviews, observation and documentation. Then to check the validity of the data that has been analyzed using data triangulation techniques. So this research concludes that strengthening the capacity of Public Relations, crisis management, and optimizing cooperation with internal units, media and external agencies need to be carried out in order to maintain and improve the reputation of the State Islamic University